2009
DOI: 10.3904/kjim.2009.24.1.76
|View full text |Cite
|
Sign up to set email alerts
|

An Antinuclear Antibody-Negative Patient With Lupus Nephritis

Abstract: Systemic lupus erythematosus (SLE) is a typical autoimmune disease that's characterized by various autoantibodies to nuclear and cytoplasmic antigens. The presence of antinuclear antibodies (ANA) in serum is generally considered a decisive diagnostic sign of SLE. However, a small subset of SLE patients who had the typical clinical features of SLE was reported to show persistently negative ANA tests. Our report describes a 16-yr-old female who presented with the clinical manifestations of SLE such as malar rash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Immunofluorescence (IF) is characteristic for the presence of the 3 classes of immunoglobulins (IgG, IgM, IgA) and classic and alternative complement pathway deposits (C3, C4, C1q) [1,7,16,[18][19][20] . Because of the widespread potential derangements, a renal biopsy is critical to making the clinical diagnosis, as the pattern of LN injury identified often dictates treatment course and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence (IF) is characteristic for the presence of the 3 classes of immunoglobulins (IgG, IgM, IgA) and classic and alternative complement pathway deposits (C3, C4, C1q) [1,7,16,[18][19][20] . Because of the widespread potential derangements, a renal biopsy is critical to making the clinical diagnosis, as the pattern of LN injury identified often dictates treatment course and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…There are reported cases of ANA negative patients, one study from korea observed the Lupus nephritis patient with ANA negativity. [15] …”
Section: Resultsmentioning
confidence: 99%
“…This finding was significantly higher than in previously published reports (2-3%). 19,20 An increased number of ANA negative patients can be explained by the technical inaccuracy in laboratories, too low levels of ANA in patient's serum, and by binding ANA in the form of immune complex. 20 The serum level of complements are found to be decreased in active disease, and is often improved with treatment in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 An increased number of ANA negative patients can be explained by the technical inaccuracy in laboratories, too low levels of ANA in patient's serum, and by binding ANA in the form of immune complex. 20 The serum level of complements are found to be decreased in active disease, and is often improved with treatment in SLE. Twenty percent of the SLE patients were of families in which one first-degree relative had lupus, probably due to the high consanguinity in the Iranian population.…”
Section: Discussionmentioning
confidence: 99%